Pipeline integrity assurance : a practical approach - Mohitpour, Mo (American Society of Mechanical Engineers, 2010)
This book will provide a wealth of technical information for those concerned with, or responsible for, the safety and integrity of pipeline systems. It addresses the full life cycle of a pipeline by considering the entire spectrum of pipeline integrity management, ranging from data gathering (tools and methods), assessment techniques (condition and risks verification), to repairs and emergency response, including incident management.
Title from PDF title page (ASME eBooks Web site, viewed 12/04/2010).
Keywords: Pipelines -- Protection.; Pipelines -- Reliability.; Pipeline failures -- Prevention.; Pipelines -- Design and construction -- Quality control.; elektronické knihy; electronic books